Conceptual Operationalisation Issues Within The Context Of An International Study: Japanese And American Firms - Ernest H. Hall, Jr.,; Jooh Lee, (Asian Academy of Management Journal, 2012)
Proper conceptualisation of key concepts is crucial to the development of any field of study. However, this is not necessarily true when it comes to the field of strategy. Although it is widely accepted that firm performance is an essential variable in the strategy literature and that diversification is the most commonly studied variable of strategy (Dess, Gupta, Hennart, & Hill, 1995) the issue of proper operationalisation is conspicuously absent. It is readily observable that there is a plethora of measures being employed to measure both diversification and firm performance. However, the measures of performance and diversification that have been employed have not been unanimously agreed upon. In addition to this general state of confusion, the issue of international variations across measures has not been evaluated. The present paper seeks to address the issues of conceptual operationalisation for performance and strategy across international boundaries.